Analisis Sistem Informasi Manajemen Barang Milik Daerah pada Dinas Perpustakaan dan Kearsipan Kota Medan - Indah Nurfi; Laylan Syafina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Developing information systems for the public interest is a necessity for an organization. The success of an organization can be determined by seeing whether the planned objectives have been achieved, each plan needs to be implemented with efficient procedures. These government tasks are closely related to management information systems, because management information systems are applications that improve government performance and are expected to help decision making, information provision, and operational procedures. One of the efforts to create a reliable management information system is by implementing the Regional Goods Management Information System Application (SIMBADA). This study aims to analyze the minutes of handover still done manually and not systemized. This research uses qualitative research methods with a descriptive approach. The results of this study indicate that there are negative and positive impacts related to the use of the SIMBADA application as well as constraints in the application that there is no category of handover minutes, so that the input process is still done manually. Where it is not efficient, it can cause data errors that can affect the performance of related work.